2016
DOI: 10.1021/acschembio.6b00596
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Mdm2-Binding Mode of the 3-Pyrrolin-2-one- and 2-Furanone-Based Antagonists of the p53-Mdm2 Interaction

Abstract: The p53 pathway is inactivated in almost all types of cancer by mutations in the p53 encoding gene or overexpression of the p53 negative regulators, Mdm2 and/or Mdmx. Restoration of the p53 function by inhibition of the p53-Mdm2/Mdmx interaction opens up a prospect for a nongenotoxic anticancer therapy. Here, we present the syntheses, activities, and crystal structures of two novel classes of Mdm2-p53 inhibitors that are based on the 3-pyrrolin-2-one and 2-furanone scaffolds. The structures of the complexes fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 51 publications
4
18
0
Order By: Relevance
“…Identified compounds bound to Mdm2 with K D values ranging from 1 to 365 µM and from 0.5 to 40.5 µM, which were determined by NMR titration of 15 N-labelled Mdm2 with compounds and MST, respectively. As in this study, large differences were also observed between K D values determined by NMR titration and MST 54 . In the other case, phage display was employed to identify peptide inhibitors of another KLIKK protease, karilysin.…”
Section: Discussionsupporting
confidence: 67%
“…Identified compounds bound to Mdm2 with K D values ranging from 1 to 365 µM and from 0.5 to 40.5 µM, which were determined by NMR titration of 15 N-labelled Mdm2 with compounds and MST, respectively. As in this study, large differences were also observed between K D values determined by NMR titration and MST 54 . In the other case, phage display was employed to identify peptide inhibitors of another KLIKK protease, karilysin.…”
Section: Discussionsupporting
confidence: 67%
“…This methodology was, for example, applied for the synthesis of new γ-hydroxy-γ-butyrolactams having a unique Mdm2-Binding mode 42 or for the synthesis of phaeosphaeride A. 43 A similar strategy, reported by Coleman and co-workers, involving allylindium species, was also used for the total synthesis of lucilactaene.…”
Section: Scheme 22 Addition Of Organometallic Reagents Onto Maleimidementioning
confidence: 99%
“…To date, there are over 20 chemotypes that have been reported as MDM2 inhibitors, such as nutlins [ 3 ], spirooxindole [ 4 ], benzodiazepinedione [ 5 ], isoquinolin-1-one [ 6 ], chromenotriazolopyrimidines [ 7 ], imidazolyl indole [ 8 ], piperidine [ 9 ], chalcone [ 10 ], diketopiperazines [ 11 ], morpholinone [ 12 ], and pyrrolin-2-one [ 13 ]. Several MDM2 inhibitors, including RG7112 [ 14 ], RG7388 [ 15 ], SAR405838 [ 16 ], AMG-232 [ 17 ], HDM201 [ 18 ], and APG-115 [ 19 ] have progressed into clinical trials.…”
Section: Introductionmentioning
confidence: 99%